Sources of acid insoluble ash as marker of corn digestibility in broilers - Santos, Edna Teles dos; Silva, Flávio Ferreira da; Barbosa, Fabrício Coelho; Carvalho, Genilson Bezerra de; Farias, Leonardo Atta; Biagiotti, Daniel; Bezerra, Roseane Madeira; Dourado, Leilane Rocha Barros (Semina: Ciências Agrárias, 2022)
The objective was to evaluate three sources of acid insoluble ash (AIA) (celite, kaolin, and sand), as indicators, to determine the apparent metabolizable energy of corn on a natural matter (AME) basis, dry matter digestibility coefficient (DMDC), and crude protein digestibility coefficient (CPDC) using total and partial excreta collection methods. Two hundred and ten Ross broiler chicks of 18 to 27 days of age were used. Broilers were adapted to experimental the diet for four days, and excreta were collected for 5 days. A reference diet (RD) based on corn and soybean meal was prepared to meet the nutritional requirements of the birds. A test diet was prepared with 40% replacement of RD with corn. The formulated diets were: D1, 99% Reference diet + 1% celite; D2, 59.4% RD + 39.6 % corn + 1% celite; D3, 99% Reference diet + 1% kaolin; D4, 59.4% RD + 39.6 % corn + 1% kaolin; D5, 99% Reference diet + 1% sand; D6, 59.4% RD + 39.6 % corn + 1% sand. The treatments were distributed in a completely randomized design, with six diets and five replicates of seven birds each in a 2x3 factorial arrangement. There were significant interactions for all variables investigated. It was observed that the AME and DMDC values of corn were similar in the two methods of collection, and CPDC values using kaolin and celite makers were similar. However, the AME and CPDC of corn using sand with partial collection method were underestimated by 17.70 and 15.53%, respectively compared to those with the total collection method. The AME values of corn with the collection methods using celite and, the DMDC using celite and sand were significantly different. It was observed that the DMDC using celite and sand provided significantly lower values (4.67 and 5.15%), respectively, and the AME using celite was 2.86% lower than that obtained by total collection. To determine the EMA, DMDC, and CPDC in broilers, it is more efficient to use celiteTM and kaolin as markers with partial collection of excreta. Sand should not be used with partial excreta collection method, because it provides lower values of AME and CPDC compared to with total excreta collection method.xos de AME e CPDC em comparação com o método de coleta total de excreta.